Axisymmetric Electromagnetic Resonant Cavity Solution by a Meshless Local Petrov-Galerkin Method - Soares, Ramon D.; Moreira, Fernando J. S.; Mesquita, Renato C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This work describes a meshless approach to obtain resonant frequencies and field distributions in axisymmetric electromagnetic cavities. The meshless local Petrov-Galerkin is used with shape functions generated by moving least squares. Boundary conditions are imposed by a collocation method that does not require integrations. The proposed analysis has simple implementation and reduced computational effort. Results for TE and TM modes of cylindrical and spherical cavities are presented and compared with analytical solutions.